A Case Report On Alopecia Areata – A Comprehensive Clinical Analysis - P. Akhila; K. Vedith Reddy; S. Veena; K. Harshitha; Dr. B. Ramadevi; Dr. K. Tirumala Naik (International Journal of Scientific Research in Science and Technology, 2025)
Alopecia areata (AA) is an autoimmune disorder characterized by non-scarring hair loss, which can significantly impact patients’ psychological well-being. This case report presents an 11-year-old female patient with a sudden onset of alopecia areata, discussing clinical presentation, diagnostic approach, management, and prognosis. The patient exhibited multiple non-scarring alopecic patches on the scalp, confirmed by a positive pull test. Treatment with systemic immunosuppressants, including cyclosporine and methylprednisolone, led to significant hair regrowth over three months. This case highlights the importance of early diagnosis and individualized treatment to achieve optimal outcomes in paediatric patients with alopecia areata.
Keywords: alopecia areata; autoimmune disorder; alopecia totalis; alopecia universalis; cyclosporine; prednisolone